Antiseizure medications for primary and secondary seizure prevention after stroke - Wolcott, Zoe C.; Freund, Brin E.; Tatum, William O.; Feyissa, Anteneh M. (Frontiers in Neurology, 2025)
Post-stroke seizures (PSS) and post-stroke epilepsy (PSE) are serious complications of cerebrovascular disease, contributing to morbidity, delayed recovery, cognitive decline, and mortality. PSS are classified as early (within 7 days) or late (after 7 days), with late-onset seizures often signaling the development of PSE. As stroke survival improves, the incidence of PSS continues to rise. Risk factors include cortical involvement, large or severe strokes, and early seizures. Although antiseizure medications (ASMs) are central to management, their use is limited by a lack of high-quality trials and reliable predictive tools. Routine primary prophylaxis is generally discouraged, except in high-risk patients—such as those with hemorrhagic stroke or severe cortical damage—while secondary prophylaxis after unprovoked seizures remains standard. Evidence supporting specific ASMs is limited, but lamotrigine and levetiracetam are considered reasonable first-line options. ASM selection should be individualized, particularly in older adults or those with cardiovascular or cognitive comorbidities, for whom older, enzyme-inducing ASMs carry greater risks. Withdrawal is often recommended after early seizures, but managing established PSE remains challenging without validated biomarkers. High-quality trials are urgently needed to evaluate the efficacy, safety, and tolerability of ASMs in post-stroke seizure prevention. Advancing the field also requires robust validation studies, improved prediction models, and personalized treatment strategies. This minireview summarizes current approaches to ASM use in PSS, with an emphasis on clinical decision-making for initiation and discontinuation.